Civil-military conflict in Imperial Russia, 1881-1914 - Fuller, William C. (Princeton legacy library., 2014)
This book is a full-scale study in English of tsarist civil-military relations in the last decades of the Russian Empire. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found.